Self-Compassion and Physical Activity in Relation to Women’s Experiences with Breast Cancer - Rogers, Kim A.; Mitchell, Erin; Cardinal, Bradley J. (Applied Behavioral Health and Psychology, 2026)
An understudied phenomenon in behavioral health is the role of self-compassion in relation to physical activity among women with breast cancer. Therefore, this study aimed: (a) to understand sources of suffering in the context of managing breast cancer, including issues associated with, and opportunities afforded by, physical activity; and (b) to document the interplay between the personal meaning attributed to self-compassion and physical activity involvement. Guided by a relativist ontology perspective, semi-structured interviews were conducted with 18 women (37–75 years of age). The severity of cancer ranged from Stage 0 to Stage 3. Thematic analysis of the data generated three themes reflecting the experiences that contribute to suffering for women with breast cancer—challenges related to self, challenges related to others, and challenges related to physical activity. In addition, three themes represented women’s relationship with self-compassion and physical activity involvement—strained, developing, and part of one’s life. In general, women who experienced self-compassion as more integral to their lives tended to engage in physical activity as a means of self-care, adjust their activity levels to align with their abilities, embrace where they were physically, and view their activity from a new perspective. The findings from this study support the role of self-compassion as a healthy coping strategy for women who have been diagnosed with breast cancer. Healthcare providers, public health officials, and physical activity professionals can reinforce and support self-compassion through appropriate policies, programs, and services, particularly those that foster understanding and build accommodating physical activity environments.